2019
DOI: 10.3389/fmicb.2019.01626
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Loaded Polymethylmethacrylate Beads and Spacers in Treatment of Orthopedic Infections and the Role of Biofilm Formation

Abstract: Polymethylmethacrylate (PMMA) also referred as (acrylic) bone cement is a non-degradable biomaterial that has been used in clinical orthopedic practice for several decades. PMMA can be used in a plain formulation, but is often used in an antibiotic-loaded formulation in (primary and revision) arthroplasty and in treatment of orthopedic infections as prosthetic joint infections (PJI) and chronic osteomyelitis. In treatment of PJIs antibiotic-loaded PMMA is often used as a carrier material for local antibiotic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
154
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 98 publications
(110 reference statements)
2
154
0
3
Order By: Relevance
“…The most popular local treatment is an antibiotic-eluting material called polymethyl methacrylate (PMMA) or 'bone cement' [17]. This has been referred to as the gold-standard of chronic osteomyelitis treatment [17,18]. Experimental studies have shown that PMMA can deliver in the order of 200 times the amount that systemic antibiotics are able to [19].…”
Section: Polymethyl Methacrylatementioning
confidence: 99%
See 1 more Smart Citation
“…The most popular local treatment is an antibiotic-eluting material called polymethyl methacrylate (PMMA) or 'bone cement' [17]. This has been referred to as the gold-standard of chronic osteomyelitis treatment [17,18]. Experimental studies have shown that PMMA can deliver in the order of 200 times the amount that systemic antibiotics are able to [19].…”
Section: Polymethyl Methacrylatementioning
confidence: 99%
“…In addition, the high temperatures generated during the preparation of PMMA can degrade its antibiotic content and induce thermal necrosis. This means certain antibiotics such as tetracyclines cannot be used [18]. Others have described a rare 'bone cement implantation syndrome' with PMMA use [24].…”
Section: Polymethyl Methacrylatementioning
confidence: 99%
“…As the number of total joint replacements increases, so does the risk of infection around the prosthesis. 2,3 PJI can be divided into bacterial and fungal infections according to the different pathogenic organisms involved. The main bacterial pathogens are Staphylococcus aureus and S. epidermidis, 5 while the most common fungal pathogen is Candida albicans.…”
Section: Characteristics Of Prosthesis-related Infectionsmentioning
confidence: 99%
“…2,3 Due to the protection provided by the biofilm, the bacteria inside the biofilm are very difficult to kill. 2 Therefore, effectively destroying the biofilm becomes a key aim of the treatment of PJI. Many studies have shown that GE, as a naturally occurring antibacterial substance, has a good antibiofilm effect.…”
Section: Characteristics Of Prosthesis-related Infectionsmentioning
confidence: 99%
See 1 more Smart Citation